Obesity, Smoking, Physical Activity, Hypertension: Models of Stroke Causes in South Sulawesi Province - Awal, Muhammad; Ashriady, Ashriady; Durahim, Darwis; Adam, Adriyani (Al-Sihah: The Public Health Science Journal, 2021)
Lifestyle changes have led to an increase in cases of non-communicable diseases in Indonesia, including hypertension and stroke. Unhealthy eating behavior, smoking habits, alcohol consumption, stress, and lack of physical activity are risk factors for degenerative diseases, besides the other risk factors such as age, gender, and heredity. This research aimed to determine the factor of obesity, smoking behavior, physical activity, and hypertension on the incidence of stroke in South Sulawesi Province. The method of research was analytic observational with a case-control approach. The case group was stroke patients as many as 750 cases and the control group was non-stroke patients as many as 750 cases. Data analysis using Path analysis. The results showed that there was a significant relationship between stroke and hypertension with a path coefficient value of 0.33, the relationship between physical activity and the incidence of stroke through hypertension with a path coefficient value of 0.13, obesity and the incidence of stroke through hypertension with a path coefficient value of 0, 21, there is a relationship between smoking and the incidence of stroke through hypertension with a path coefficient value of 0.08. Hypertension is a risk factor that directly affects the incidence of stroke compared to other risk factors. however, all of these risk factors can be reduced, especially by doing routine and regular physical activity every day.